Pengaruh Kompetensi, Akuntabilitas, Pengendalian Internal dan Partisipasi Masyarsakat terhadap Kinerja Pemerintah Desa Kebalandono - Desy Ramadhan Kumalasari; Tituk Diah Widajantie (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the effect of competence, accountability, internal control and community participation on the performance of the Kebalandono village government. The research method used is a quantitative method. The sampling technique used in this research is simple random sampling. This study uses primary data with data collection using a questionnaire method that will be filled out by the people of Kebalandono Village. The analysis technique uses Partial Least Square (PLS) with WarpPLS 7.0 software. The Structural Equation Model (SEM) analysis method consists of two sub-models, namely the structural model (inner model) and the measurement model (outer model). Based on the test results, it can be concluded that Competence has no effect on the performance of the village government, Accountability affects the performance of the Kebalandono Village government, Internal Control affects the performance of the Kebalandono Village government. Community participation has an effect on the performance of the Kebalandono Village government.